Performance analysis of network-on-chip topologies. Issue 6 (18th August 2017) - Kumar, Ana; Tyagi, Shivam; Jha, C. K.
Abstract: Network on chip architecture provides a way to design complex integrated circuits with an objective to reduce connection issues, design productivity, and energy utilization. Network performance of a network is calculated by various factors but throughput is the most dominant characteristic for measuring network performance. So, this work includes investigation of various NoC topologies and analysis is done on basis of average throughput and average latency for ensuring network performance.